Psilocybe cubensis: neuropsychopharmaceutical potential of psilocybin and psilocin - Barrientos-Alfaro, Frank (2024)
Fungi play a key role in maintaining life on Earth, as they perform multiple ecological functions. Besides, they are producers of various secondary metabolites, among these, alkaloids, which in certain cases can provide hallucinogenic properties. Psilocybe cubensis is a common species of hallucinogenic mushrooms known as “magic mushrooms”. This species of the phylum Basidiomycota, native to Mesoamerica, produces alkaloids such as psilocybin and its dephosphorylated derivative, psilocin. The potential of these compounds in the treatment of various illnesses such as depression, anxiety, attention deficit disorder, post-traumatic stress disorder, and obsessive-compulsive disorder has been studied. Mushrooms that accumulate psilocybin are usually not toxic for consumption, but they can have side effects such as nausea, vomiting, headache, increased heart rate, and blood pressure. Given this and legal limitations, this mushroom and its compounds are not available in the market; however, new research demonstrates their potential and why their commercialization should be considered.